2018
DOI: 10.1016/j.ccell.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Programming of Schwann Cells by Lats1/2-TAZ/YAP Signaling Drives Malignant Peripheral Nerve Sheath Tumorigenesis

Abstract: Malignant peripheral nerve sheath tumors (MPNSTs) are highly aggressive Schwann cell (SC)-lineage-derived sarcomas. Molecular events driving SC-to-MPNST transformation are incompletely understood. Here, we show that human MPNSTs exhibit elevated HIPPO-TAZ/YAP expression, and that TAZ/YAP hyperactivity in SCs caused by Lats1/2 loss potently induces high-grade nerve-associated tumors with full penetrance. Lats1/2 deficiency reprograms SCs to a cancerous, progenitor-like phenotype and promotes hyperproliferation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 47 publications
10
92
0
Order By: Relevance
“…YAP (Yes-associated protein) and TAZ (Transcriptional coactivator with PDZ-binding motif), are paralogous transcription coactivators, chiefly known as potent stimulators of cellular proliferation in diverse developing (von Gise et al, 2012; Zhang et al, 2012; Xin et al, 2013; Cotton et al, 2017) and neoplastic (Yu et al, 2015; Zanconato et al, 2016; Moon et al, 2018) tissues. Consistent with this role, we and others have recently shown that YAP/TAZ promote vigorous proliferation of immature Schwann cells (SC) in developing peripheral nerves (Poitelon et al, 2016; Deng et al, 2017; Grove et al, 2017), and that overexpression of YAP/TAZ promotes tumorigenic proliferation of mature SCs in adult peripheral nerves (Mindos et al, 2017; Wu et al, 2018). Unexpectedly, several groups demonstrated that YAP or YAP/TAZ promote differentiation of developing SCs by upregulating myelin-associated genes, thereby mediating developmental myelination (Fernando et al, 2016; Lopez-Anido et al, 2016; Poitelon et al, 2016; Deng et al, 2017; Grove et al, 2017).…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations
“…YAP (Yes-associated protein) and TAZ (Transcriptional coactivator with PDZ-binding motif), are paralogous transcription coactivators, chiefly known as potent stimulators of cellular proliferation in diverse developing (von Gise et al, 2012; Zhang et al, 2012; Xin et al, 2013; Cotton et al, 2017) and neoplastic (Yu et al, 2015; Zanconato et al, 2016; Moon et al, 2018) tissues. Consistent with this role, we and others have recently shown that YAP/TAZ promote vigorous proliferation of immature Schwann cells (SC) in developing peripheral nerves (Poitelon et al, 2016; Deng et al, 2017; Grove et al, 2017), and that overexpression of YAP/TAZ promotes tumorigenic proliferation of mature SCs in adult peripheral nerves (Mindos et al, 2017; Wu et al, 2018). Unexpectedly, several groups demonstrated that YAP or YAP/TAZ promote differentiation of developing SCs by upregulating myelin-associated genes, thereby mediating developmental myelination (Fernando et al, 2016; Lopez-Anido et al, 2016; Poitelon et al, 2016; Deng et al, 2017; Grove et al, 2017).…”
Section: Introductionsupporting
confidence: 65%
“…YAP/TAZ are located in the nuclei of developing SCs, where they promote proliferation and differentiation (Poitelon et al, 2016; Deng et al, 2017; Grove et al, 2017). They are also nuclear and transcriptionally active in adult SCs that maintain the myelin sheath (Grove et al, 2017) and that proliferate abnormally (Wu et al, 2018). It was therefore particularly intriguing to find that YAP/TAZ become undetectable in denervated SCs, and that they reappear as axons regenerate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, clinical case studies of patients with concurrent NF1-induced tumors and Charcot-Marie Tooth disease have been reported in the literature suggesting a possible overlap in underlying biology [40][41][42] . While the role of EGR2 in Schwann cell differentiation is still under active investigation [43] , EGR2-driven pathways have been found to be significantly downregulated in Lats1/2 deficient Schwann cell based MPNST models [44] . Furthermore, EGR2 expression in immune cells has been shown to be important for activation of M1/M2 macrophages [45] as well as regulation of CD4+ T cells [46] .…”
Section: Discussionmentioning
confidence: 99%